Risk Factors of Behavioral Problems in Pediatric Epilepsy - Nur, Fadhilah Tia; Azmi, Nurul; Hermasari, Bulan Kakanita (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Epilepsy is the most common neurological disorders in children and the number of case for epilepsy still increasing. Epilepsy can affect children and their growth physically, psychologically, and socially, yet the treatment of behavioral problems in pediatric epilepsy is still lacking. This study aimed to investigate the association of frequency of seizure, type of seizure, duration of illness, and use of antiepileptic drug with behavioral disorder in children with epilepsy.Subjects and Method: This was an analytical observational study with a cross sectional design. The study was conducted at Pediatric Neurology Unit of Dr. Moewardi hospital, Surakarta, from September to October 2016. A sample of 50 pediatric patients with epilepsy was selected for this study. Parents or caregivers completed behavioral problems screening tool Pediatric Symptom Checklist-17 (PSC-17) and were interviewed about frequency of seizure, type of seizure, duration of illness, and use of antiepileptic drug. The data were analyzed by a multiple logistic regression.Results: Frequent seizure (OR= 3.09; 95% CI= 0.89 to 10.59; p= 0.068) increased behavioral problem. Being treated with ≥1 anti-epileptic drugs (OR= 1.58; 95% CI= 0.44 to 5.71; p= 0.521) increased behavioral problem, but it was statistically non-significant. Type of seizure (OR= 1.01; 95% CI= 0.32 to 3.20; p= 0.991) and duration of illness ≥1 year (OR= 1.03; 95% CI= 0.22 to 4.89; p= 1.000) were not associated with behavioural problem. Conclusion: Frequent seizure increase behavioral problemKeywords: epilepsy, behavioral problems, pediatricsCorrespondence: Fadhilah Tia Nur. Department of Child Health, Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: fadhilah.harris@gmail.comIndonesian Journal of Medicine (2020), 05(02): 162-169https://doi.org/10.26911/theijmed.2020.05.02.11